Fine-grained privacy operation control method for layout documents - Peijie YIN; Fenghua LI; Ben NIU; Haiyang LUO; Bin KUANG; Lingcui ZHANG (Tongxin xuebao)
In view of the problem of privacy information disclosure caused by uncontrolled forwarding in the context of frequent exchange of privacy information, a fine-grained privacy operation control method for layout documents was proposed, which could achieve differentiated fine-grained privacy operation control according to the requirements of the sharer during the sharing process of privacy information.For the received multimodal layout document, the existing privacy operation control strategy was extracted, which combined the current sharer’s use attribute and the receiver’s privacy protection ability and other factors.The privacy operation control strategy was generated iteratively, and an abstract control strategy generation algorithm framework was given.Based on the iterative privacy operation control strategy and combined with specific operation scenarios, the differentiated data-masking control, exchange boundary control and local use control were carried out for different modes of information components, and the abstract privacy operation control algorithm framework was given.A prototype system for privacy operation control of OFD (open fixed-layout document) was developed to verify the above algorithms.The generation and delivery of iterative privacy operation control strategy based on friendship, as well as the differential data-masking control, exchange boundary control and local use control of OFD were implemented in the instant messaging system.